An alternative maximum reach strategy for routine immunization during the pandemic in Indonesia - Purwito, Dedy (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Immunization plays a significant role in reducing the mortality rate for children under five. Immunization has been proven to be an efficient and effective health effort in preventing and reducing morbidity, disability, and death due to diseases that can be prevented by immunization. Increasing the coverage of immunization needs to be considered by the government by involving the community and health offices, and other stakeholders.Â  Health centers should provide immunization services considering the immunization guidelines during the Covid-19 pandemic, ensuring adequate health workers (vaccinators).Â  Provide information about safe immunization services and coordination and collaboration with stakeholders (private and public sectors).